STATUS OF AND THREATS TO MICROHABITATS OF THE ENDANGERED ENDEMIC BANGGAI CARDINALFISH (Pterapogon kauderni) - Samliok Ndobe; Abigail Mary Moore; Jamaluddin Jompa (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The endemic Banggai cardinalfish (Pterapogon kauderni) is one of conservation priority marine species in Indonesia. With a conservation status of Endangered, Indonesia has made a commitment to P. kauderni conservation, and policy development is underway. P. kauderni lives in symbiosis with sea urchins (Diadema sp.), sea anemones and branching corals. This research evaluated the current status of and threats to P. kauderni microhabitat, including the climate change context. Primary data were collected using Coral-Watch and swim survey methods during the 2016 global bleaching event, and compared with survey data collected since 2004. The study revealed a sharp decline in Diadema sp. population abundance as well as reduced sea anemone abundance, in both cases largely due to sharp increases in exploitation by local communities, mostly for human consumption. Corals and other microhabitats had also suffered from increased coral reef degradation related to local-scale destructive human activities, as well as climate-related coral bleaching. Wherever microhabitat availability was greatly reduced, P. kauderni abundance had declined sharply, irrespective of fishing pressure on this species. Microhabitat protection and recovery is considered a sine qua non prerequisite for successful in-situ P. kauderni conservation. The results contribute to the scientific basis for sustainable management of endemic P. kauderni stocks and habitat. Keywords Endangered species; symbiosis; microhabitat; overfishing; coral bleaching